A New Highly Anisotropic Rh‐Based Heusler Compound for Magnetic Recording. Issue 45 (7th October 2020) - He, Yangkun; Fecher, Gerhard H.; Fu, Chenguang; Pan, Yu; Manna, Kaustuv; Kroder, Johannes; Jha, Ajay; Wang, Xiao; Hu, Zhiwei; Agrestini, Stefano; Herrero‐Martín, Javier; Valvidares, Manuel; et al.
Abstract: The development of high‐density magnetic recording media is limited by superparamagnetism in very small ferromagnetic crystals. Hard magnetic materials with strong perpendicular anisotropy offer stability and high recording density. To overcome the difficulty of writing media with a large coercivity, heat‐assisted magnetic recording was developed, rapidly heating the media to the Curie temperature T c before writing, followed by rapid cooling. Requirements are a suitable T c, coupled with anisotropic thermal conductivity and hard magnetic properties. Here, Rh2 CoSb is introduced as a new hard magnet with potential for thin‐film magnetic recording. A magnetocrystalline anisotropy of 3.6 MJ m −3 is combined with a saturation magnetization of μ0 M s  = 0.52 T at 2 K (2.2 MJ m −3 and 0.44 T at room temperature). The magnetic hardness parameter of 3.7 at room temperature is the highest observed for any rare‐earth‐free hard magnet. The anisotropy is related to an unquenched orbital moment of 0.42 μB on Co, which is hybridized with neighboring Rh atoms with a large spin–orbit interaction. Moreover, the pronounced temperature dependence of the anisotropy that follows from its T c of 450 K, together with a thermal conductivity of 20 W m −1 K −1, make Rh2 CoSb a candidate for the development of heat‐assisted writing with a recording density in excess of 10 Tb in. −2 . Abstract : Rh2 CoSb is introduced as a potential hard magnet for heat‐assisted magnetic recording. The hardness parameter of 3.7 is the highest observed for any rare‐earth‐free hard magnet. The temperature dependence of the anisotropy, together with the high anisotropic thermal conductivity of 20 W m −1 K −1, makes Rh2 CoSb a candidate for heat‐assisted writing with a high recording density.